2012
DOI: 10.4236/cm.2012.31012
|View full text |Cite
|
Sign up to set email alerts
|

A Hypothetical Anti-Aging Mechanism of “Yang-Invigorating” Chinese Tonic Herbs

Abstract: Chinese tonic herbs are generally classified into Yin and Yang categories based on their health-promoting action. Emerging evidence has suggested that in addition to up-regulating mitochondrial functional status, Yang tonic herbs also enhance cellular/mitochondrial antioxidant capacity, and may thus prevent age-related diseases and prolong the healthy part of lifespan (i.e. healthspan). The proposed biochemical mechanism underlying the antioxidant action of Yang tonic herbs involves a sustained and low level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…The proposed biochemical mechanism underlying the antioxidant action of Yang tonic herbs involves a sustained and low level of mitochondrial ROS production, which is secondary to the increased activity of the ETC, with the possible involvement of mitochondrial uncoupling. "Yang invigoration" improves antioxidant defense in the body in the long term and thereby offers a promising prospect for preventing or possibly delaying age-related diseases and the detrimental effects of aging [62]. Studies from various laboratories showed that Yang tonic herbs produced antioxidant actions by free radical-scavenging, inhibition of oxidant production, inhibition of NADPH-dependent lipid peroxidation and increase of antioxidant enzyme activities, with a resultant protection against oxidative tissue damage.…”
Section: Qi-invigoration and Yang-invigorationmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed biochemical mechanism underlying the antioxidant action of Yang tonic herbs involves a sustained and low level of mitochondrial ROS production, which is secondary to the increased activity of the ETC, with the possible involvement of mitochondrial uncoupling. "Yang invigoration" improves antioxidant defense in the body in the long term and thereby offers a promising prospect for preventing or possibly delaying age-related diseases and the detrimental effects of aging [62]. Studies from various laboratories showed that Yang tonic herbs produced antioxidant actions by free radical-scavenging, inhibition of oxidant production, inhibition of NADPH-dependent lipid peroxidation and increase of antioxidant enzyme activities, with a resultant protection against oxidative tissue damage.…”
Section: Qi-invigoration and Yang-invigorationmentioning
confidence: 99%
“…According to TCM theory, a deficiency of Yang is believed to be one of the causative factors for the development of Parkinson's disease (PD), a common neurodegenerative disease that severely compromises the quality of life in many elderly individuals [68]. Based on the finding that ViNeuro can enhance the mitochondrial ATP generation capacity (a "Yang-invigoration" property), it is plausible that the relief of Parkinsonian symptoms involves an improvement of cellular energy status that eventually leads to an enhancement of neuronal function [62].…”
Section: Qi-invigoration and Yang-invigorationmentioning
confidence: 99%